Genetically Modified Rabbits for Cardiovascular Research - Fan, Jianglin; Wang, Yanli; Chen, Y. Eugene (Frontiers in Genetics, 2021)
Rabbits are one of the most used experimental animals for investigating the mechanisms of human cardiovascular disease and lipid metabolism because they are phylogenetically closer to human than rodents (mice and rats). Cholesterol-fed wild-type rabbits were first used to study human atherosclerosis more than 100 years ago and are still playing an important role in cardiovascular research. Furthermore, transgenic rabbits generated by pronuclear microinjection provided another means to investigate many gene functions associated with human disease. However, owing to the lack of embryonic stem cells and genome information of rabbits, for a long time, it has been a dream for scientists to use knockout rabbits generated by homologous recombination-based genomic manipulation as in mice. This obstacle has greatly hampered using genetically modified rabbits to disclose the molecular mechanisms of many diseases. The advent of genome editing technologies has dramatically extended the applications of experimental animals including rabbits. In this review, we will update genetically modified rabbits, including transgenic, KO and knock-in rabbits during the past decades regarding their use in cardiovascular research and point out the perspectives in future.